Perancangan Game Survival Horror “Kepunan” Menggunakan Unity Game Engine - M Jevon Lee; Meiyi Darlies; Fithri Selva Jumeilah (Jurnal Teknologi Informatika Multimedia Digital, 2025)
Gaming is a structured activity performed during leisure time, either alone or with others, with the primary aim of entertaining and challenging users. The horror game genre is particularly captivating as it evokes fear and expresses a chilling atmosphere. To date, there are no games set in historical locations in Palembang, specifically the Japanese Cave, which features dark corridors and profound mysteries. This research aims to design a horror game themed around the Japanese Cave, utilizing historical elements and a tense atmosphere as the game’s setting. The methods employed include creating a Game Design Document (GDD) covering Game Overview, User Interface Design, Level Design, World Design, Content Design, and System Design, as well as implementing pixel art style to create a nostalgic feel. Additionally, the finite state machine (FSM) method is applied to enhance gameplay dynamics and responsiveness. The game development also follows the Game Development Life Cycle (GDLC) method, encompassing phases of planning, design, development, testing, and launch to ensure the quality and effectiveness of the game. The result of this project is the development of a game titled "Kepunan,"